Digitalization of the Notary Profession in the Era of Economic and Business Globalization - Noviana, Ninik; Arpangi, Arpangi (Jurnal Hukum Khaira Ummah, 2025)
The rapid development of technology today has brought significant changes in various sectors, including the world of law, economy and business. One innovation in the legal field that can be applied is the concept of cyber notary or digital notary. The profession of Notary is closely related to the business world, at least this is shown from the mechanism for determining the need (formation) of Notaries in an area based on (a) business activities, (b) population, (c) the average number of deeds made each month. The influence of the business world on the availability of the number of Notary formations proves that there is a close relationship between the position of Notary and the business world. This data analysis method includes a qualitative approach by conducting a study of laws and regulations to explain the legal problems of written law in the implementation of cyber notary. The data collection technique used is library research, which involves collecting data from various academic sources and official documents. This library study will provide a strong theoretical and contextual basis for understanding the development of cyber notary and the challenges of digitalization faced by the notary profession. The results of the study obtained are that cyber notary has great potential to improve the ease of doing business in Indonesia by accelerating the notarization process, reducing costs, and increasing accessibility. However, to achieve this potential, clear regulations and a broad understanding of the legal validity of digital documents are needed. With the right support, cyber notary can be an effective tool to encourage economic growth and ease of doing business in Indonesia in the era of economic and business globalization.